The Relationship between Body Mass Index and Grasping Strength in Students of the Medical Education Study Program, Faculty of Medicine, University of Papua - Erwin Ramandei; Yanti Pesurnay; Oktamina Pinem; Irmayanti Irmayanti; Devi Darwin (Majalah Kesehatan Indonesia, 2022)
Grip strength as a clinical parameter to assess a person's nutritional status. Body mass index is useful for describing body composition. Differences in Body Mass Index (BMI) values can affect motor performance, postural balance, hand grip muscle strength and quality, lifestyle, physical activity, age and gender. The type of research carried out in this research is observational research, namely by observing students of PSPD FK UNIPA. The observation method used in this study is a cross-sectional observation method. Data collection was carried out in June 2022 using the simple random sampling method. There were 107 samples, the results of which were analyzed by using the Chi-Square test. The results of this study showed that the average number of overweight students was 34 people with a percentage of 31%, normal students amounted to 51 people with a percentage of 47.7% while underweight was 22 people with a percentage of 20.6%. The average grip strength, the respondents with strong gripping strength were 39 people with a percentage of 36.44%, for normal there were 53 people with a percentage of 49.54% while the weak were 15 people with a percentage of 14.02%. The results of the Chi-Square test showed that the significant value of 2-tailed was 0.734 more than 0.05. There is no statistically significant relationship between body mass index and grip strength in PSPD FK UNIPA students.